Larval parasitoids occurring on Maruca vitrata Fabricius (Lepidoptera: Pyralidae) in Benin, West Africa - Arodokoun, D.Y.; Tamo, Manuele; Cloutier, C.; Brodeur, J. (Elsevier, 2006)
The larval parasitoid guild of the cowpea pod borer Maruca vitrata was studied on wild and cultivated host plants in Southern and Central Benin, West Africa. A total of eight parasitoids, seven of which belonging to the Hymenoptera: Braconidae, and one to the Diptera: Tachinidae, were observed exploiting larvae of M. vitrata. All guild parameters observed in this study, i.e. richness, composition and structure, were found to vary according to host plant species. Detailed analysis of the latter allowed the identification of key parasitoid species, which substantially contribute to M. vitrata larval mortality. The two most important parasitoids were the braconids Phanerotoma leucobasis and Braunsia kriegeri, which were observed all year round on various host plants. Average parasitism rates inflicted by P. leucobasis and B. kriegeri on M. vitrata larvae collected from the most commonly occurring wild host plants (Pterocarpus santalinoides, Lonchocarpus sericeus and L. cyanescens, all Fabaceae) were 30.2 and 4.2%, respectively. On M. vitrata larvae collected from the main cultivated host, Vigna unguiculata (cowpea), parasitism rates were 5.6% for P. leucobasis and 4.9% for B. kriegeri. These results are discussed in the context of future strategies for biological control of M. vitrata.